Acid Treatment on Carbonate Rock: An Effect of HCL Concentration on Rock Properties and Fluid Flowrates - Nugroho, Agung; Amanah, Nur Layli; Kamal, Hary Perdana; Angkasa, Syahreza (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2022)
A series of analyses techniques were performed to study the influence of different acid concentrations on the rock properties during the acidizing process. Based on the Thin section and Routine Core Analysis (RCA), the calcite content have effect on the reservoir quality from the aspect of rock-fluid properties. In this paper, the physical and mineralogical responses to rock acidizing of carbonate rock are evaluated. This study found that calcite content decreases approximately 25% from the total calcite content of rock samples after the addition of HCl. Scanning Electron Microscope (SEM) Analysis show that samples treated using HCl 15% provide a wider pore size distribution, resulting in the increasing permeability fluid flow rate